Smart phone apps for medical tablets identification I (apps development) - Tun, Soe Zarni (2019)
In recent technological advanced years, smartphones have become an essential part in our daily lives. It has been proven time after time that smartphones and its functions are very useful and a massive help to society. With growing advances in the society in every aspect, there has been tremendous improvements and new findings in pharmaceutical fields every day. Countless types of medicines in forms of tablets, capsules, liquids, etc... are scattered around in public each day. Given the fact that having numerous types of medical tablets all over the place, it is almost impossible for a layman to identify the medicine once the tablets are being separated from the packaging. Thus, this project aims to develop a smartphone application to identify the medical tablets. In this project, the database has been developed and implemented for medicines that data were collected. Basic user interface of the application has been implemented for the identifying and classification of medicines. In this report, it has been discussed intensively on what the author has done as well as the results achieved for this project.